2018
DOI: 10.3389/fmicb.2018.02184
|View full text |Cite
|
Sign up to set email alerts
|

Using ‘Omic Approaches to Compare Temporal Bacterial Colonization of Lolium perenne, Lotus corniculatus, and Trifolium pratense in the Rumen

Abstract: Understanding rumen plant–microbe interactions is central for development of novel methodologies allowing improvements in ruminant nutrient use efficiency. This study investigated rumen bacterial colonization of fresh plant material and changes in plant chemistry over a period of 24 h period using three different fresh forages: Lolium perenne (perennial ryegrass; PRG), Lotus corniculatus (bird’s foot trefoil; BFT) and Trifolium pratense (red clover; RC). We show using 16S rRNA gene ion torrent sequencing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
6
15
0
Order By: Relevance
“…It is possible that increases in abundance of members of this genus may have been responsible, at least in part, for the improved digestive efficiency observed. Increases in this genus have been identified previously when providing perennial ryegrass to an in vitro model of rumen fermentation (Elliott et al, 2018) and Pseudobutyrivibrio has also been identified as a native rumen bacterium that holds potential as a rumen probiotic, due to its ability to modulate in vitro fermentation to improve energy yields (Fraga et al, 2014). As Pseudobutyrivibrio has been shown to increase linearly with increasing NDF and ADF in the diet (Li et al, 2019), it is possible that the substrate provided to the model had higher proportions of these than the diet consumed by the animal.…”
Section: Discussionmentioning
confidence: 85%
“…It is possible that increases in abundance of members of this genus may have been responsible, at least in part, for the improved digestive efficiency observed. Increases in this genus have been identified previously when providing perennial ryegrass to an in vitro model of rumen fermentation (Elliott et al, 2018) and Pseudobutyrivibrio has also been identified as a native rumen bacterium that holds potential as a rumen probiotic, due to its ability to modulate in vitro fermentation to improve energy yields (Fraga et al, 2014). As Pseudobutyrivibrio has been shown to increase linearly with increasing NDF and ADF in the diet (Li et al, 2019), it is possible that the substrate provided to the model had higher proportions of these than the diet consumed by the animal.…”
Section: Discussionmentioning
confidence: 85%
“…The hypothesis that changes in the secondary metabolism of ruminal bacteria will depend on growth conditions and the composition of the rumen microbiome was confirmed by analyzing the metatranscriptome of the microbiota attached to perennial ryegrass incubated in ruminal fluid. Previous studies based on the differences in diversity of the bacteria attached to perennial ryegrass demonstrated that colonization events follow a primary (up to 4 h) and secondary pattern (after 4 h) (Colman et al 2016;Mayorga et al 2016;Elliott et al 2018). Our data on the expression of the NRPS and PKS genetic machinery confirmed that the biosynthesis of secondary metabolites by ruminal bacteria follow the main changes occurring between primary and secondary colonization of perennial ryegrass, with an significant increase in the expression of the NRPS and PKS functional domains between 4 to 8 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, the ability of ruminants to utilize cellulolytic and hemicellulolytic feedstuff distinguishes them from monogastric farm animals. Degradation of plant material in the rumen requires colonization of ingested plant material by a complex microbial consortium and occurs in a timedependent manner that is influenced by the nature of the substrate ingested (Elliott et al, 2018). The resulting consortia functions synergistically to degrade the substrate, with cross feeding between microbes such that the rate and extent of degradation is greater than that could be accomplished by a microbial monoculture (Krause et al, 2013).…”
Section: Rumen Fermentationmentioning
confidence: 99%
“…Among dietary interventions, we can distinguish between those aimed at improving forage quality and changing the proportion of the diet, and those aimed at using feed additives to supplement the diet. Molecular techniques based on either amplicon sequencing of ribosomal genes or whole metagenome sequencing (Huws et al, 2018) are increasingly allowing us to explore both the temporal and spatial development of microbial populations within the rumen that are related to the colonization and degradation of dietary fibre entering the rumen (Elliott et al, 2018). We have shown that shifts in the carbohydrate and protein content of diets consumed (Belanche et al, 2012) and less obvious changes, such as the method of forage preservation and type of forage (Huws et al, 2018), affect feed colonization by rumen microbes and subsequent digestion.…”
Section: Factors That Influence the Rumen Microbiomementioning
confidence: 99%